Strategies to promote safe mobilization of people with obesity in inpatient care settings: A scoping review protocol - Rebecca A. Roberts; Elizabeth Finkelzon; Anika Younker; Georgia Merriman; Paul Claveria; Julianna Lancaster; Christopher Farley; Anastasia N. L. Newman (PLoS ONE, 2026)
Introduction Hospital-associated deconditioning is common during inpatient admissions, particularly among patients with obesity whose mobilization presents added complexity and safety challenges. Despite the known benefits of mobilization, there is no comprehensive synthesis or guidelines to address safe mobilization for patients with obesity in inpatient settings. Materials and methods This protocol describes a scoping review that will systematically map the literature on mobilization strategies used for adults with obesity in acute and inpatient rehabilitation settings, including barriers and facilitators to safe practice. Following the Joanna Briggs Institute methods and PRISMA-ScR reporting, peer-reviewed studies involving patients with author-defined obesity will be identified through comprehensive searches of Ovid MEDLINE, Ovid Embase, Ovid Emcare, Ovid AMED, EbscoHost CINAHL, and Clarivate Web of Science from database inception. Screening and data extraction will be conducted independently by two reviewers, with discrepancies resolved by consensus or a third reviewer. Data will be summarized narratively and with descriptive statistics, as appropriate. Conclusion The results of this scoping review will summarize the available evidence on the strategies used to safely mobilize patients with obesity during admission to inpatient settings and the barriers and facilitators that impact these strategies. A manuscript will be submitted for publication in a peer-reviewed journal and presented at appropriate rehabilitation conferences.